2015
DOI: 10.4103/2152-7806.157308
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive tubular access for posterior cervical foraminotomy

Abstract: Background:Minimally invasive tubular access for posterior cervical foraminotomy can be an effective and safe technique for decompression of the nerve root utilizing minimally invasive muscle splitting with routine outpatient discharge. This technique has come under scrutiny calling into question the associated learning curve, a subjective limited exposure provided, and an argument that the risks and complications are largely unknown. In response to previously published critiques, this study aims to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 14 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Other studies from the Asian population have shown similar results demonstrating that the presence of BIM deletion polymorphism is a negative predictive factor of response rate, PFS and OS to EGFR TKIs [24, 25, 27]. In a meta-analysis of six original eligible studies including 871 NSCLC patients [29], patients BIM del+ had poor response to EGFR TKI therapy (p= 0.001, OR = 0.39; 95% CI = 0.23–0.67). Disease control rate (DCR) with EGFR TKI treatment was significantly decreased in BIM del+ patients (p= 0.007, OR = 0.46, 95% CI = 0.25–0.85).…”
Section: Discussionmentioning
confidence: 83%
“…Other studies from the Asian population have shown similar results demonstrating that the presence of BIM deletion polymorphism is a negative predictive factor of response rate, PFS and OS to EGFR TKIs [24, 25, 27]. In a meta-analysis of six original eligible studies including 871 NSCLC patients [29], patients BIM del+ had poor response to EGFR TKI therapy (p= 0.001, OR = 0.39; 95% CI = 0.23–0.67). Disease control rate (DCR) with EGFR TKI treatment was significantly decreased in BIM del+ patients (p= 0.007, OR = 0.46, 95% CI = 0.25–0.85).…”
Section: Discussionmentioning
confidence: 83%
“…In breast cancer, overexpression of HER2 is found in approximately 10%–30% of patients and is associated with reduced survival [ 30 ]. In addition, EGFR deletion can also be detected in malignant gliomas, NSCLC, breast cancer, medulloblastoma and ovarian cancer [ 31 , 32 ]. The most common EGFR deletion mutant is EGFR VIII.…”
Section: Ptk and Tumormentioning
confidence: 99%
“…As a result, our meta-analysis of these studies also reflected this finding. Although several previous meta-analyses9,3336 mentioned similar findings regarding PFS, the current pooled analysis containing more eligible studies further provided a possibility to analyze other clinical outcome measures. As a comprehensive meta-analysis of PFS, OS, ORR and DCR with the largest sample size to date, our study provided a more reliable answer regarding the impact of BIM polymorphism status on treatment efficacy of EGFR-TKIs in advanced and metastatic NSCLC patients with EGFR mutations.…”
Section: Discussionmentioning
confidence: 64%